A review of thermographic techniques for damage investigation in composites - Laura Vergani; Chiara Colombo; Flavia Libonati (Fracture and Structural Integrity)
The aim of this work is a review of scientific results in the literature, related to the application of thermographic techniques to composite materials. Thermography is the analysis of the surface temperature of a body by infrared rays detection via a thermal-camera. The use of this technique is mainly based on the modification of the surface temperature of a material, when it is stimulated by means of a thermal or mechanical external source. The presence of defects, in fact, induces a localized variation in its temperature distribution and, then, the measured values of the surface temperature can be used to localize and evaluate the dimensions and the evolution of defects. In the past, many applications of thermography were proposed on homogeneous materials, but only recently this technique has also been extended to composites. In this work several applications of thermography to fibres reinforced plastics are presented. Thermographic measurements are performed on the surface of the specimens, while undergoing static and dynamic tensile loading. The joint analysis of thermal and mechanical data allows one to assess the damage evolution and to study the damage phenomenon from both mechanical and energetic viewpoints. In particular, one of the main issues is to obtain information about the fatigue behaviour of composite materials, by following an approach successfully applied to homogenous materials. This approach is based on the application of infrared thermography on specimens subjected to static or stepwise dynamic loadings and on the definition of a damage stress, ?D, that is correlated to the fatigue strength of the material. A wide series of experimental fatigue tests has been carried out to verify if the value of the damage stress, ?D, is correlated with the fatigue strength of the material. The agreement between the different values is good, showing the reliability of the presented thermographic techniques, to the study of composite damage and their fatigue behaviour.